Novel and efficient Cu-based catalyst constructed by lignite alkali-oxygen oxidation products for selective aerobic oxidation of alcohols to aldehydes. (1st December 2019) - Sha, Yufei; Li, Na; Zhi, Keduan; Song, Yinmin; Liu, Quansheng; Zhou, Huacong
Graphical abstract: Highlights: A novel approach to utilize lignite alkali-oxygen oxidation products (AOOPs) is proposed. AOOPs could be directly used to construct Cu-AOOPs catalyst without tedious purification. Cu-AOOPs catalyst is effective for selective catalytic oxidation of various alcohols compounds under mild conditions. Abstract: Developing efficient and clean utilizing route of low-ranked lignite is a highly desirable and significant topic in view of value-added utilization of coal resources. Depolymerizing lignite into water-soluble fractions is a promising route for lignite utilization, but how to use the depolymerized mixtures efficiently becomes a critical issue for promoting the application of this route. In this study, the raw lignite was depolymerized by alkali-oxygen oxidation, and the water-soluble alkali-oxygen oxidation products (AOOPs) were directly used without tedious purification to construct novel Cu-AOOPs catalysts for aerobic oxidation of alcohols into aldehydes. Both the preparation conditions of the catalysts and the reaction parameters during the catalytic reaction were systematically studied. The structures of the catalysts were characterized in detail by SEM, TEM, Power XRD, FT-IR, XPS, TG, ICP-OES and BET. The results showed that the proposed route was feasible to prepare Cu-AOOPs catalysts for alcohol oxidation using depolymerized mixtures from lignite. The obtained Cu-AOOPs catalysts were highly efficient for the selective oxidation of benzyl alcohol, and both the conversion of benzyl alcohol and the yield of benzaldehyde could reach up to 90% under mild temperature (<100 °C) and atmospheric oxygen pressure. The Cu-AOOPs catalyst could be reused for at least 6 times without significant changes in performance and structures, indicating the catalyst had excellent stability during the oxidation reaction. Besides benzyl alcohol, the Cu-AOOPs catalyst was proved to be effective for alcohols with different structures. The strategy of using AOOPs from lignite as raw materials to construct catalysts not only provides a potential way for the value-added utilization of low rank coals but also broadens the sources of raw materials for constructing metal catalysts.